2015
DOI: 10.1287/mnsc.2014.1935
|View full text |Cite
|
Sign up to set email alerts
|

Competition in Portfolio Management: Theory and Experiment

Abstract: W e explore theoretically and experimentally the general equilibrium price and allocation implications of delegated portfolio management when the investor-manager relationship is nonexclusive. Our theory predicts that competition forces managers to promise portfolios that mimic Arrow-Debreu (AD) securities, which investors then combine to fit their preferences. A weak version of the capital asset pricing model (CAPM) obtains, where state prices (relative to state probabilities) implicit in prices of traded sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The experimental finance literature (e.g., Bossaerts and Plott, 2004) has consistently found that prices converge towards their equilibrium values, even in difficult scenarios (Asparouhova et al, 2015). Our study extends that work by introducing an ETF index asset.…”
Section: Introductionsupporting
confidence: 75%
“…The experimental finance literature (e.g., Bossaerts and Plott, 2004) has consistently found that prices converge towards their equilibrium values, even in difficult scenarios (Asparouhova et al, 2015). Our study extends that work by introducing an ETF index asset.…”
Section: Introductionsupporting
confidence: 75%
“…It is uncertain to which extent social comparisons and competition play any role in the last cited studies. The results of the other studies except Asparouhova et al (2015) still show that performance-based incentives may increase risk taking with the consequence that assets are mispriced. Increasing the number of prizes in a tournament and penalties are factors that seem to counteract increased risk taking.…”
Section: Risk Taking Induced By Performance-based Incentives In Experimental Asset Marketsmentioning
confidence: 85%
“…Experimental asset markets (Noussair and Tucker, 2013;Palan, 2013) In noting the increased supply of funds resulting in competition among fund companies to attract investor money, Asparouhova et al (2015) ask what effects this may have on trading and asset prices. In an experiment lasting for six one-week periods, 32 participants (reported to be homogenous in skill and information access) play the role of managers of different funds.…”
Section: Risk Taking Induced By Performance-based Incentives In Experimental Asset Marketsmentioning
confidence: 99%